TREATMENT- A PERSPECTIVE IN SOCIAL WORK AND A CHALLENGE FOR SOCIAL WORKERS - Trajkov, Ivan (Ревија за социјална политика/Journal of Social Policy, 2015)
The field of social work in Macedonia was developed in severalstages; in each of these there has been advancement in education andprofessional development of social workers. The role of a social workerin the past would be more in administration day, they are analysts andresearchers who, coping with the modern day issues and theconsequences of the social existence of the growing number ofindividuals and groups, are facing the challenges of using new modes ofassistance and improving the mental and social state of users. Their lineof work implies dealing with individuals and groups of various ages, withvarious problems (misconduct, substance abuse, post-violence effect,stress, mental illness), which, among others, are the result of thedetrimental influence of the family and wider social setting, thus creatingthe need to use alternative therapeutic methods and techniques inreducing the negative social impact.